ENGLISH SILENT LETTERS PRODUCED BY NEW ENGLISH LEARNERS CAN DESTROY THE STANDARD ENGLISH PRONUNCIATION - Amran, Ali; Saragih, Mandra (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
This research tries to investigate, analyse why new English learners produce English silent letters when they communicate. There are many new leaners of English can easily produce some non-standard English pronunciation dealing with those silent letters which may lead English Expert misinterpret the meaning which finally misunderstand take place. This study also focuses on the standard English pronunciation based on either British or American English pronunciation. Winda P., at al, agree that one thing that always happened in the errors of speaking English is silence in a letter. They define silent letter as a letter which is not pronounced in a word, it is present in spelling but missed in pronunciation. While Podhaizer (1998), states that the silent letters are letters which are not sounded. Therefore, English learners, when facing with silent letter words, were often confused about the pronunciation. New learners don not realize that they make mistake in pronouncing several words when they communicate in English. English silent letters are that you must write that letter in some particular words, but you must not read it. If you do not write it the words is not complete and it is wrong word in terms of spelling. Then if you pronounce it, based on you un-conscious knowledge, automatically you then produce non-standard English pronunciation. Most new learners commonly make mistake in pronouncing the following words: For examples the words half, doubt, debt, combing, climbing, plumber and so on. Musa Abubakar clarifies that perfect pronunciation as one of the effective language skills in communication greatly affects teaching, learning and usage of English as a second language because it enhances transfer of information from source to target. Further, Bishnu P.M. defines that English is an un phonetic language. There is no match between the letter that we write and the sound we produce. Finally, the writer tries to list those silent letters derived from several different academic resources.